Оптимальні характеристики грунтових теплообмінників для теплонасосних систем опалення - Безродний, Михайло Костянтинович; Притула, Наталя Олександрівна (НТУ "ХПІ", 2017)
Визначено раціональні співвідношення між характеристиками горизонтального/вертикального ґрунтового теплообмінника (ГТО/ВГТО), таких як довжина труби одного контуру/глибина свердловини, діаметра труби, швидкості руху теплоносія в нижньому контурі теплонасосної системи (ТНС) в залежності від умов роботи ГТО/ВГТО та ТНС. Дані характеристики повинні забезпечити оптимальну швидкість теплоносія в нижньому контурі ТНС, що дозволить отримати мінімальні питомі затрати електроенергії на ТНС теплопостачання в цілому.

The rational relation between the characteristics of horizontal/vertical ground heat exchangers (HHE/VHE), in particular the pipe length of one loop/ the well depth, heat carrier speed in the lower loop of heat pump system (HPS) was determined depending on HHE/VGHE and HPS operation conditions (an intensity of heat removal from the ground). These characteristics must provide an optimal speed for the heat carrier in a lower loop of the HPS, which allows for the definition of minimum specific power costs for the heat-pump heating system on the whole. Numerical studies based on the analysis of the set of equations for the expenditures of energy and the thermal balance of individual elements of heat –pump circuit showed that the optimal speed values of heat carrier and the minimum specific expenditures of external power for the HPS heating are available and on the basis of this the relations between the characteristics of ground heat exchangers that provide minimum total power expenditures for the HPS heating were defined. It has been established that at high values of the well depth the use of pipes with a minor diameter becomes unreasonable due to high hydraulic losses. Hydraulic losses are essentially increased with an increase in the well depth at high values of heat flow from the ground that requires the use of the pipes of a major diameter for the heat exchanger. It has been established that at an optimal speed of the heat carrier in the lower loop specific power expenditures for the HPS heating with vertical ground heat exchangers in the entire range of VGHE parameters are within 0.275, which corresponds to the value of conditional transformation coefficient of HPS for the low temperature water heating of at least 3.6 and it is indicative of a sufficient efficiency of the system.
Optimal characteristics of ground heat exchangers for the heat-pump heating system
Keywords: насос тепловий; енергозатрати; енергія зовнішня; heat pump; ground heat exchanger; low temperature heating system; expenditures; external power